New Generation of Small Incision Lenticule Extraction (SMILE) Procedure for Myopic Astigmatism with High Astigmatism Value : A Case Series: Poster Presentation - Case Series - General practitioner - Putri, Rizqi Suryani; Dharmawidiarini, Dini; Moenir, Farida; Napitupulu, Sahata P . H. (Majalah Oftalmologi Indonesia, 2023)
Introduction : Myopic astigmatism is a refractive disorder which could cause visual impairment especially with high astigmatism value. It affects patients’ productivity and quality of life. The management for myopic astigmatism is challenging because no consensus on the ideal method was reached. Case Illustration : Case 1: 19-year-old male with Uncorrected Visual Acuity (UCVA) 3/60 in the right eye with a manifest refraction of S-3.25 C-2.00 x 0 and 2/60 in the left eye with a manifest refraction S-5.50 C-0.50 x 0. Case 2: 18-year-old male with UCVA 3/60 in both eyes with a manifest refraction of S-3.00 C-2.25 x 5 and S-2.50 C-2.00 x 0. Case 3: 18-year-old male with UCVA 3/60 in both eyes witha manifest refraction of S-2.75 C-2.00 x 0 and S-2.50 C-2.25 x 180. Slit lamp, fundus examination, corneal topography, tomography, epithelial thickness profile, and aberrometry were within normal limits. The patients underwent SMILE using Visumax 800 Femtosecond laser with 3-4 mm incision at 120°, optical zone between 6-6.8 mm and cap thickness between 100-120 ?m. Discussion : In this case series, SMILE was chosen because studies described SMILE as an effective and safe refractive procedure compared to Femtosecond Laser-assisted in situ keratomileusis (FS-LASIK). Target refraction is emmetropia without cyclotorsion adjustment, it showed that post operative UCVA in all eyes were 6/6 using Snellen chart and none of the eyes loss the BCVA. Conclusion : New Generation of SMILE as management of myopic astigmatism with high astigmatism value shows good result improving visual outcomes.